TRADISI PANGAN LOKAL SUKU MALIND PAPUA DALAM MENUMBUHKAN KESADARAN SEJARAH MELALUI PEMBELAJARAN KREATIF - Sormin, Salman Alparis; Supriatna, Nana; Sundawa, Dadang; Gyta Sari Harahap, Dharma (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2024)
This research began with concerns about the degradation of the local Malind tribe community in South Papua amidst the frenzy of development. The low level of historical awareness of the Malind generation has led to their marginalization amidst development. Therefore, creativity is needed in learning to raise awareness of the history of the Malind tribe generation. This research is a literature study research. Data was obtained from literature sources, books, journals, documents and other literature sources. Processing research data using the Miles and Huberman technique. From the analysis of the data obtained, it was found that the Malind tribal community has a rich tradition of maintaining balance between humans and the environment. In meeting their food needs, the Malind tribe utilizes nature in a balanced manner. The Malind tribe's food sources include sago, bananas, wild boar, deer, fish, stocks, cassowaries and other animals obtained through hunting. The Malind tribe's food is processed by burning and boiling without using food flavorings. The local food traditions of the Malind tribe can be used as material to foster historical awareness through integration in learning. Teacher creativity is needed in utilizing the traditions and environment of the Malind tribe in designing learning.The conclusion of this research is that the Malind tribe's tradition of obtaining food is a tradition that must be taught to students in developing their historical awareness. Teachers must integrate history learning so that historical facts are close to the current context experienced by students.